Longitudinal Evaluation of the Structural and Functional Changes Associated with Glaucoma in Myopia. Issue 6 (June 2020) - Biswas, Sayantan; Biswas, Partha
Abstract : SIGNIFICANCE: This study ascertains that myopia is a risk factor for glaucoma progression among eyes with primary open angle glaucoma. Myopic eyes with primary open angle glaucoma may benefit from measurement and incorporation of axial length information into clinical decision making. PURPOSE: The purpose of this study was to estimate the rate of change in retinal nerve fiber layer (RNFL) thickness and the rate of change in visual field of glaucoma patients with and without myopia. METHODS: We conducted a prospective, observational cohort study where we analyzed 245 eyes of 135 glaucoma patients followed for a mean period of 6.08 years. All the subjects had RNFL imaging and standard automated perimetry performed for both eyes in the same visit every 4 months for at least 60 months. RESULTS: The rate of change of average RNFL thickness and visual field index (VFI) was −0.29 μm/y (95% confidence interval, −1.80 to +1.23 μm/y) and −0.30%/y (95% confidence interval, −2.24 to +1.64%/y), respectively, after adjusting for age, axial length, IOP, baseline RNFL thickness, signal strength, and correlation between fellow eyes. Axial length, as a continuous variable, was not associated with the rates of change of average RNFL thickness and VFI. However, high myopic eyes with axial lengths of ≥26.0 and ≥26.5 mm had an average rate of change of RNFL thickness of 0.15 and 0.16 μm/y faster than eyes with axial lengths of less than 26 and 26.5 mm, respectively. Similarly, myopic eyes with an axial length of ≥26.5 mm were associated with a 0.21%/y faster rate of VFI reduction. CONCLUSIONS: Both RNFL and visual field progression rates are faster in myopic glaucomatous eyes with an axial length of ≥26.5 mm than in eyes <26.5 mm. However, the small difference that supports high myopia as a risk factor for progression does not indicate the clinical importance or significance of axial length.